Soil porosity modelling for immersive serious game based on vertical angle, depth, and speed of tillage - Anang Kukuh Adisusilo; Mochamad Hariadi; Eko Mulyanto Yuniarno; Bambang Purwantana; Radi Radi (International Journal of Advances in Intelligent Informatics, 2018)
The real data support the “seriousness” of the serious game and give more authentic situations, which can make players feel immersed in scenarios, and gain a real experience. Therefore, the modeler must be able to recognize whether a model reflects reality to identify and deal with divergences between theory and data. In this paper, we present a model for design a basis of immersive in serious games. The studied case is the tillage using a moldboard plow, by taking real data through an experiment use a device called soil bin. It aims to determine the effect of angle, depth, and speed on the soil porosity; by comparing the value of the smallest error using the polynomial function of the use of different orders. The result of an average smallest error with the polynomial approach is 1.10E-07 in the 3rd order, closer to the experimental value. Therefore, the model can be used for designing immersive serious game.